Is DNA fingerprinting the gold standard for estimation of adoption and impacts of improved lentil varieties?. (February 2019) - Yigezu, Yigezu A.; Alwang, Jeffrey; Rahman, M. Wakilur; Mollah, M. Bazlur R.; El-Shater, Tamer; Aw-Hassan, Aden; Sarker, Ashutosh
Highlights: Improved varieties of lentils have been widely diffused in Western Bangladesh. DNA variety verification provides nuanced information necessary for analysis of adoption. Improved variety adoption does not affect farmer yield; taste, nutrition and cooking quality are main breeder objectives. Abstract: In the early 1980s, disease susceptibility in short-season lentil landraces began to limit productivity in areas where relay cropping took place in Bangladesh. Since then, several improved high-yielding lentil varieties, which are resistant to rust and blight and suitable in the relay cropping system, have been released jointly by national and international research centers. This study used three methods, namely a panel of experts, a survey of 1000 households where the respondents named the variety they used, and DNA fingerprinting of seed samples collected from all lentil plots cultivated by survey households to estimate adoption. Double hurdle and instrumental variables regression methods were applied to the household survey and DNA fingerprinting data to identify determinants of adoption and measure their impacts. Of particular interest was whether estimates of adoption, determinants of adoption and impacts varied by method of variety identification. Results showed that the expert panel overestimated the adoption of more recent varieties while about 89% of the farmer-reported varieties were accurate, as verified by DNA fingerprinting. DNA fingerprinting appears to have little advantage for estimating the level of adoption in this case, where few varieties of lentils are found, local variety names do not exist, and most seed is obtained through a formal system. However, even under these conditions, determinants of adoption vary by identification method, and use of farmer-reported information on the variety can lead to erroneous conclusions about determinants of adoption. Because recent breeding efforts have focused on taste and cooking considerations, yield impacts were not significantly different from zero.